Principles and practice of constraint programming : 24th International Conference, CP 2018, Lille, France, August 27-31, 2018, Proceedings /: 24th International Conference, CP 2018, Lille, France, August 27-31, 2018, Proceedings. (2018) - Unknown
No abstract available